Low-Density Floating PGlu–STY/EPS Immobilized Lipase Biocatalyst with Particle-Size-Controlled Architecture for Fatty Acid Ethyl Ester Production - Natta Rattanapanya; Thanaporn Jitrasing; Jittranuch Jirapathomkul; Surachai Pornpakakul (International Journal of Renewable Energy Development, 2026)
Pseudomonas cepacia lipase was immobilized onto low-density polyglutaraldehyde–styrene-coated expandable polystyrene beads (PGlu–STY/EPS) and applied as a reusable biocatalyst for biodiesel production from soybean oil via ethanolysis. The catalyst system was developed through a progressive catalyst-engineering strategy involving floating support design, support-density engineering, particle-size optimization, and coating morphology refinement to may improve catalyst distribution, interfacial accessibility, and operational stability. The immobilized lipase exhibited a protein loading yield of 71.81% and catalytic activity of 26.12 U g⁻¹-support. Smaller EPS particle sizes and optimized PGlu–STY coating conditions improved enzyme immobilization efficiency and catalytic performance by enhancing substrate accessibility and reducing diffusion limitations. Under optimized transesterification conditions, including an oil-to-ethanol molar ratio of 1:5, temperature of 40 °C, reaction time of 24 h, and the use of absolute ethanol, the maximum fatty acid ethyl ester (FAEE) conversion reached 92.8%. Biodiesel conversion was quantified using ¹H NMR spectroscopy. The immobilized catalyst maintained substantial catalytic activity over more than 10 repeated reaction cycles, indicating favorable operational stability and reusability. FT-IR analysis suggested successful covalent immobilization through Schiff-base interactions between aldehyde groups of the support and amino groups of the enzyme. The floating low-density EPS architecture may contribute to improved catalyst distribution in the heterogeneous oil/alcohol reaction medium and reduced unfavorable sedimentation in glycerol-rich regions, thereby potentially enhancing interfacial transesterification behavior. Although advanced characterization techniques such as BET, XPS, and GC–MS were not available in the present study, the combined catalytic and morphological results demonstrate that PGlu–STY/EPS supports provide a potentially useful platform for reusable immobilized lipase systems for enzymatic transesterification applications.